Small-size Jatropha Seed Biochar Extracted from Microwave Pyrolysis: Optimization of Its Biocomposites Mechanical Properties by Mixture Design - Perry Law, Nyuk Khui; Rezaur, Rahman; Kuok, King Kuok; Muhammad Khusairy, Bakri; Muhammad, Adamu; Diana, Tazeddinova; Zhumayeva A., Kazhmukanbetkyzy; Baibatyrov, Torebek (2021)
Microwave pyrolysis of finely ground jatropha seed biochar was used as bio-filler to develop biocomposites. Effects influencing the mechanical properties of the biocomposites were investigated based on varied material ratio. Ratios by percentage of weight were determined by D-optimal (custom) mixture design using the Stat Ease “Design Expert”. The mechanical properties, such as tensile strength, modulus of elasticity, and microhardness, were the dependent variables (response). Bio-filler content was optimised to attain the overall best mechanical properties for the biocomposites. The optimized biocomposite that showcased good tensile strength, modulus of elasticity, and microhardness biocomposite ratio’s predicted mechanical properties mean values were tensile strength (9.53 MPa), modulus of elasticity (0.730 GPa), and microhardness (20.4 HV) for polylactic acid and biofiller mixture; and tensile strength (7.92 MPa), modulus of elasticity (0.668 GPa), and microhardness (18.7 HV) for polylactic acid, biofiller, and poly(ethylene-alt-maleic anhydride) mixture. Models generated by the mixture design showcased some degree of noise and error present; however, the outcome through the optimization step was generally reliable for predicting the mechanical properties. Additional data gathered through experimental testing and replicates could improve the reliability of the model.